Monica Genesin, Karl Gerhard Hempel, Thede Kahl (eds.), Endangered Language Varieties in Italy and the Balkans, Vienna, Austrian Academy of Sciences Press, 2024, 379 p. - Falaleev, Pavel (Helsinki Romanian Studies Journal, 2025)
Both Italy and the Balkans are regions with a linguistic mosaic that has greatly interested the research community. This article reviews the book titled Endangered Languages Varieties in Italy and the Balkans, which provides insight into some issues concerning certain minority languages in the two regions. These issues include terminology, legislation, linguistic landscape, the vitality of minority languages, and language contact. Despite some minor incoherences, the book is a valuable contribution to research on endangered languages in Europe.